Contribution of GPD2/mGPDH to an alternative respiratory chain of the mitochondrial energy metabolism and the stemness in CD133‐positive HuH‐7 cells. (16th January 2020) - Mikeli, Maimaiti; Fujikawa, Makoto; Nagahisa, Kai; Yasuda, Shuhei; Yamada, Natsuhiko; Tanabe, Tsutomu
Abstract: HuH‐7 cells, derived from human hepatocarcinoma, are known to contain the CD133‐positive cancer stem cell populations. HuH‐7 cells showed higher ATP synthesis activity through the respiratory chain compared to another human hepatocarcinoma cell line HepG2 and showed an especially higher glycerol‐3‐phosphate (G3P)‐driven ATP synthesis (G3P‐ATPase) activity. We found that the CD133‐positive HuH‐7 cells expressed high levels of GPD2 (glycerol‐3‐phosphate dehydrogenase or mGPDH) and showed high G3P‐ATPase activity. Next, to elucidate the relationship between CD133 and GPD2, we inhibited downstream factors of CD133 and found that a p38 inhibitor decreased the expression of GPD2 and decreased the G3P‐ATPase activity. Furthermore, GPD2‐knockdown (GPD2‐KD) cells exhibited strong reduction of the G3P‐ATPase activity and reduction of lactic acid secretion. Finally, we validated the effect of GPD2‐KD on tumorigenicity. GPD2‐KD cells were found to show decreased anchorage‐independent cell proliferation, suggesting the linkage of G3P‐ATPase activity to the tumorigenicity of the CD133‐positive HuH‐7 cells. Inhibition of G3P‐ATPase disrupts the homeostasis of energy metabolism and blocks cancer development and progression. Our results suggest inhibitors, targeting GPD2 may be potential new anticancer agents. Abstract : GPD2 controls G3P‐ATPase activity that constitutes an alternative respiratory chain X and is found to be important for the stemness of CD133‐positive HuH‐7 cells.